Asia: The Wood and the Trees - Khoo, Kay Kim (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
“Asia” is the term which can confuse more than enlighten. That, geographical refers to a huge land mass – the largest of the continents - does not pose a problem, boundary disputes between or among Asian countries notwithstanding. However, its ethnic diversity (its inhabitants account for about 56% of the world’s total population) is mind-boggling. There are significant differences not only among the people of the numerous nation-states located in Asia but also among territorial groups which belong to the same state, for instance, between the Kerinci of Sumatra and the Banjarese of Kalimantan who are bothlikely to be unknown to people outside the Malay Archipelago.